Influence of laminar plasma quenching on rolling contact fatigue behaviour of high-speed railway wheel steel. (August 2020) - Zhang, Qingsong; Toda-Caraballo, Isaac; Dai, Guangze; Feng, Zongli; Li, Qiuze; Yu, Deping
Graphical abstract: Highlights: LPQ produced a hardened layer and residual compressive stresses prolonging RCF life. The RCF life increase linearly with the depth of HAZ. The critical depth of HAZ affecting the RCF crack growth is 1 mm. Strain induced retained austenite transformed into twin martensite for LPQ steel. Slip induced sub-grains for the untreated steel. Abstract: This study aims at determining the influence of laminar plasma quenching (LPQ) on the rolling contact fatigue (RCF) behaviour under water condition of high-speed railway wheel steel. The wheel and rail test rollers were treated by LPQ with different scanning speeds (700, 900, 1100, 1300 mm/min), which generated different depth of heat affected zones (HAZs) and residual compressive stresses in the surface layer. To obtain an insight of the microstructures and their corresponding thermal treatment applied, the temperature evolution was simulated during the LPQ by Finite Element Modelling and the micro-structures of cross-sections below the roller surfaces were characterized. The results showed martensite, retained austenite and undissolved cementite in the HAZ as a consequence of the ultrafast heating and cooling rates. The produced residual compressive stresses resulted in an increase of 30% of the RCF life indicating that LPQ could effectively improve the RCF resistance. Further investigations showed that the high density dislocation martensitic structure of the HAZ of reduced the plastic deformation, which could delay the RCF crack initiation and decrease the depth of RCF crack growth. During the RCF test, some retained austenite of the LPQ treated wheel roller transformed into twin martensite under the effect of strain induced martensitic transformation. The plastic deformation in the untreated wheel roller resulted in a refined microstructure showing lots of sub-grains generated in both pearlite and ferrite regions. Furthermore, we have observed that the lattice structures of the martensite in the LPQ treated sample and sub-grains of the plastically deformed untreated sample were similar to the BCC structure of the ferrite at the substrate in the high-speed railway wheel steel. We conclude from the obtained results that the LPQ processing enhances the RCF life and that this improvement is influenced by the obtained microstructure in the HAZ.